LWT - Språkbanken Text (University of Gothenburg, 2024)
Loan Word Typology list

Lånordstypologi
LWT
Keywords: Language Technology (Computational Linguistics); lexicon; Natural Language Processing; Språkbehandling och datorlingvistik